3x-12+5x=2x+4(x-3)

Simple and best practice solution for 3x-12+5x=2x+4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-12+5x=2x+4(x-3) equation:


Simplifying
3x + -12 + 5x = 2x + 4(x + -3)

Reorder the terms:
-12 + 3x + 5x = 2x + 4(x + -3)

Combine like terms: 3x + 5x = 8x
-12 + 8x = 2x + 4(x + -3)

Reorder the terms:
-12 + 8x = 2x + 4(-3 + x)
-12 + 8x = 2x + (-3 * 4 + x * 4)
-12 + 8x = 2x + (-12 + 4x)

Reorder the terms:
-12 + 8x = -12 + 2x + 4x

Combine like terms: 2x + 4x = 6x
-12 + 8x = -12 + 6x

Add '12' to each side of the equation.
-12 + 12 + 8x = -12 + 12 + 6x

Combine like terms: -12 + 12 = 0
0 + 8x = -12 + 12 + 6x
8x = -12 + 12 + 6x

Combine like terms: -12 + 12 = 0
8x = 0 + 6x
8x = 6x

Solving
8x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8x + -6x = 6x + -6x

Combine like terms: 8x + -6x = 2x
2x = 6x + -6x

Combine like terms: 6x + -6x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 0.5(x-12)=14 | | 4(9+c)=3(c-3) | | 6+1/5*5=7 | | 3(c-2)=4+2c | | 4x+7y=19 | | 1/3=6 | | -3(n+4)=-4n | | -3(n+4)=4n | | 4z+2-2z=3+z+6 | | -13+x=x+24 | | 314=13(x-2)-(12x-13)-2(150+x) | | -7(y+2)=1-6y | | 11x+6=9999999999999999999999999999999999999999999999999999999999888888888888888887 | | .5(2x-6)-2(3x+1)=10 | | 5z-7=7z-3z | | -8-9=3x+5+2x | | 1/2(5x+9)=7x | | 10=6x-7 | | 7-5z=32 | | -8(2t-(4-7))= | | (3y+2)dx-(5x-7)dy=0 | | 15x+-10=-9x+2 | | -9x-9y=0 | | 1=0.4x-0.6x-17 | | 4x+3x-6-6=10+3 | | 3x^2=3-4x | | -3n+5n=38 | | x=2500-5x | | 3.5-h=42 | | w=y(r+A) | | 3.5+42=h | | 14k-5=65 |

Equations solver categories